(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of study was to assess the knowledge and practices of mothers regarding ARI having children below 5 years of age, attending Pediatric outpatient department, Bahawal Victoria Hospital, Bahawalpur. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted in Pediatric outpatient Department, Bahawal Victoria Hospital, Bahawalpur from 13 May 2016 to 13 June 2016. Materials and Methods: The data was collected through a pre-formed questionnaire about knowledge of mothers regarding episodes and symptoms of ARI while last portion was about practices of mothers regarding treatment of ARI. Data was entered and analyzed using SPSS 13. All result was presented in percentages and in frequencies. Results: In this study 100 mothers were included, out of which 10% had poor knowledge, 72% were having satisfactory knowledge while 18% had good knowledge regarding ARI. Out of 100 mothers 23% had poor practices, 36% had satisfactory practices and 41 % had good practices regarding ARI. Conclusion: The study reveals that most of the mother had satisfactory of good knowledge about ARI. Half of the mothers know all the dangerous symptoms of ARI. However, only half of the mothers had good practices regarding ARI. Utilization of health services was moderate.